2021
DOI: 10.2147/tcrm.s286952
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of Tolvaptan in the Treatment of Autosomal Dominant Polycystic Kidney Disease

Abstract: Autosomal dominant polycystic kidney disease constitutes the most prevalent hereditary kidney disease, associated with high rates of morbidity leading eventually to end-stage renal disease. Tolvaptan is a selective vasopressin antagonist and has emerged as a promising therapeutic option for patients with autosomal dominant polycystic kidney disease. The present review summarized current evidence regarding the safety profile of tolvaptan in patients with the disease. Consistent with its pharmacological action, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
(68 reference statements)
3
8
0
Order By: Relevance
“…In parallel, Pkd1 RC/RC mice were given Tolvaptan, a selective vasopressin receptor 2 (V2) antagonist that is currently the only FDA approved drug for treatment of ADPKD ( 53, 54 ) and has a different mechanism of action than centrosome clustering inhibitors. Similar to the 2-month treatment plan, the mice showed no adverse effects to CCB02, whereas Tolvaptan-treated animals showed significant weight loss over that 5-month period (Figure 5B), which has been previously reported as a significant side effect of this compound ( 54, 55 ). Treatment with CCB02 resulted in preservation of kidney size, reduced cyst index and cyst number compared to control Pkd1 RC/RC , and better than the Tolvaptan treated group (Figure 5C-G and Supplemental Figure 5, A and B).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…In parallel, Pkd1 RC/RC mice were given Tolvaptan, a selective vasopressin receptor 2 (V2) antagonist that is currently the only FDA approved drug for treatment of ADPKD ( 53, 54 ) and has a different mechanism of action than centrosome clustering inhibitors. Similar to the 2-month treatment plan, the mice showed no adverse effects to CCB02, whereas Tolvaptan-treated animals showed significant weight loss over that 5-month period (Figure 5B), which has been previously reported as a significant side effect of this compound ( 54, 55 ). Treatment with CCB02 resulted in preservation of kidney size, reduced cyst index and cyst number compared to control Pkd1 RC/RC , and better than the Tolvaptan treated group (Figure 5C-G and Supplemental Figure 5, A and B).…”
Section: Resultssupporting
confidence: 73%
“…The copyright holder for this preprint this version posted November 17, 2022. ; https://doi.org/10.1101/2022.11.16.516801 doi: bioRxiv preprint receptor 2 (V2) antagonist that is currently the only FDA approved drug for treatment of ADPKD (53,54) and has a different mechanism of action than centrosome clustering inhibitors. Similar to the 2-month treatment plan, the mice showed no adverse effects to CCB02, whereas Tolvaptan-treated animals showed significant weight loss over that 5-month period (Figure 5B), which has been previously reported as a significant side effect of this compound (54,55).…”
Section: Inhibition Of Centrosome Clustering Attenuates Cystic Diseas...supporting
confidence: 72%
See 1 more Smart Citation
“…[ 20 22 ] Some studies have demonstrated that TLV increases the serum UA level by decreasing its renal clearance. [ 23 ] Furthermore, water intake increased in these studies, which effectively reduced urinary UA supersaturation. [ 24 ] However, our results demonstrated that adding TLV to targeted drug and traditional diuretic therapies decreased the serum UA level, perhaps because the patients’ water intake increased.…”
Section: Discussionmentioning
confidence: 90%
“…At all those trials, the doses of tolvaptan were approximately between 15 mg and 60 mg in a day. Above this dosage and also prolonged usage were reported to cause liver dysfunction via toxicity because tolvaptan is mainly metabolized by CYP3A4 [11,37]. All these trials were conducted with higher concentrations of tolvaptan treatment in patients; therefore, our results of cellular toxicity cannot be compared with these trials because our results are more meaningful for very small dosages of tolvaptan which could be measured in the cell culture system.…”
Section: Discussionmentioning
confidence: 99%